Development and Usability Testing of the Society for Pediatric Anesthesia Pedi Crisis Mobile Application. (December 2019) - Clebone, Anna; Strupp, Kim M.; Whitney, Gina; Anderson, Michael R.; Hottle, Jeffrey; Fehr, James; Yaster, Myron; Schleelein, Laura E.; Burian, Barbara K.; Galvez, Jorge A.; Lockman, Justin L.; Polaner, David; et al.
Abstract : When life-threatening, critical events occur in the operating room, the fast-paced, high-distraction atmosphere often leaves little time to think or deliberate about management options. Success depends on applying a team approach to quickly implement well-rehearsed, systematic, evidence-based assessment and treatment protocols. Mobile devices offer resources for readily accessible, easily updatable information that can be invaluable during perioperative critical events. We developed a mobile device version of the Society for Pediatric Anesthesia 26 Pediatric Crisis paper checklists—the Pedi Crisis 2.0 application—as a resource to support clinician responses to pediatric perioperative life-threatening critical events. Human factors expertise and principles were applied to maximize usability, such as by clustering information into themes that clinicians utilize when accessing cognitive aids during critical events. The electronic environment allowed us to feature optional diagnostic support, optimized navigation, weight-based dosing, critical institution-specific phone numbers pertinent to emergency response, and accessibility for those who want larger font sizes. The design and functionality of the application were optimized for clinician use in real time during actual critical events, and it can also be used for self-study or review. Beta usability testing of the application was conducted with a convenience sample of clinicians at 9 institutions in 2 countries and showed that participants were able to find information quickly and as expected. In addition, clinicians rated the application as slightly above "excellent" overall on an established measure, the Systems Usability Scale, which is a 10-item, widely used and validated Likert scale created to assess usability for a variety of situations. The application can be downloaded, at no cost, for iOS devices from the Apple App Store and for Android devices from the Google Play Store. The processes and principles used in its development are readily applicable to the development of future mobile and electronic applications for the field of anesthesiology.